A little beyond Bela's mirror - Ventura, Susana Ramos (Literartes, 2020)
Essay that analyzes the fairy tale “Beauty and the Beast” by Jeanne-Marie Leprince de Beaumont, first published in 1756 to think about the book Le magasin des enfants and the various possibilities showed by the tale